Performance analysis of rear under run protection device (RUPD) on truck based on vehicle safety standards in Indonesia - Ethys Pranoto; Edi Purwanto (Universitas Negeri Yogyakarta, 2026)
The rear under-run protection device is an apparatus installed on goods vehicles with a rear section that is more than 700 millimeters above the road surface. The height disparity between two vehicles may lead to the passenger compartment of a smaller vehicle colliding with and sliding under the chassis of a larger vehicle. This device is mounted to reduce the risk of fatalities resulting from rear-end collisions. This study aims to evaluate the design of rear under-run protection devices on goods vehicles to determine whether they meet the prerequisites set forth in the applicable Indonesian regulations. This is achieved by conducting modeling and testing simulations using software based on the finite element method. The evaluation results indicate that the underrun protection design satisfies several required technical criteria; however, non-conformities remain in structural dimensions and joint integrity, including a cross-member height of 80 mm (< 100 mm), a member length of 2200 mm (< 2300 mm), a cross-bar deflection reaching 419.5 mm (exceeding the ≤ 400 mm limit), and the use of welded joints instead of the required bolt–nut connections. Consequently, structural and mounting system modifications are necessary to achieve full compliance with the applicable standards.